2006
DOI: 10.1677/joe.1.06417
|View full text |Cite
|
Sign up to set email alerts
|

Both N-terminal and C-terminal regions of steroid sulfatase are important for enzyme activity

Abstract: Steroid sulfatase (STS) is localized in the endoplasmic reticulum and catalyzes desulfation of 3 -hydroxysteroid sulfates. X-linked ichthyosis (XLI) is an inherited skin disorder caused by deficiency of STS enzyme activity. We previously reported a case in which XLI with a one-base change in the STS gene and variation in amino acid Q560P developed. In this study, we performed molecular analysis to determine the importance of terminal regions of STS and the effect of mutant STS on STS enzyme activity. To examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…To quantify STS protein in the breast tissue samples studied, we performed western blots of tissue extracts. A specific band corresponding to the Mr of dimeric STS [51] was detected in all breast tissues investigated (Fig. 2).…”
Section: E 1 S-sulfatase (Sts) Protein Expression and Localizationmentioning
confidence: 89%
“…To quantify STS protein in the breast tissue samples studied, we performed western blots of tissue extracts. A specific band corresponding to the Mr of dimeric STS [51] was detected in all breast tissues investigated (Fig. 2).…”
Section: E 1 S-sulfatase (Sts) Protein Expression and Localizationmentioning
confidence: 89%
“…Accumulation of fatty alcohol has been shown in cultured fibroblasts and in plasma from SLS patients [1]. Numbers of mutations of FALDH gene have been shown, although only three mutations have been identified in Japanese SLS patients [2][3][4]. We here report a SLS patient who is a homozygote for one of the known mutations.…”
mentioning
confidence: 93%
“…Up to 90% of the described mutations of this gene are complete deletions, which is one of the highest percentages of chromosomal deletions among all genetic disorders [2,3]. STS is located on Xp22.3 and encodes a 62kDa polypeptide [4]. In the skin STS is expressed within the epidermis and is thought to have a role in steroid production and lipid metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Digestion of STS by endoglycosidase H shows that at least two (Asn47 and Asn259) of the STS N-glycosylation sites are used for glycosylation. It has also been reported that although both the N-terminal region and the C-terminal region of the STS enzyme are important for the STS enzymatic function (Sugawara et al, 2006), the key catalytic residue in sulphatase is a unique C-formylglycine, which is generated from a cysteine precursor. The C-formylglycine functions as a nucleophilic aldehyde hydrate in the initial addition reaction of sulphate ester hydrolysis (von Figura et al, 1998).…”
Section: Introductionmentioning
confidence: 99%